Reading Promotion Projects in the São Paulo Subway (Intercom - Brazilian Journal of Communication Sciences, 2023)
According to Augé (2012), the subway is essentially a non-place; however, through practices such as reading, its use can be resemanticized to the point of being transformed into a place. Based on this perspective and Roger Chartier’s (1996) and Michel de Certeau’s (1998) notion of reading, this work aims to observe and investigate the extent to which the various projects to encourage reading carried out in the São Paulo - SP metro produce places and non-places. The actions studied here, whether from the public or private sector, were selected because they promote the circulation of books and the practice of reading in this means of transportation. The data was collected through field research, interviews, and a documentary survey, including virtual sources. Based on the theoretical framework and the information analysis, we noticed that only a few of the initiatives actually contribute to creating a place where people can stay and get closer to culture.
Keywords: Reading practice; Book; São Paulo subway; Non place